2018
DOI: 10.1080/1028415x.2018.1556896
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness and cost-utility analysis of a group-based diet intervention for treating major depression – the HELFIMED trial

Abstract: Cost effectiveness and cost-utility analysis of a group-based diet intervention for treating major depression-the HELFIMED trial,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Similarly, systematic reviews of economic modelling studies on comparative cost-effectiveness of conventional versus integrative treatments of many health conditions (including mental illness), suggest that integrative treatments are cost-effective, and in some cases, provide cost savings [42]. Individual lifestyle interventions have also demonstrated cost-effectiveness [98,99]. Finally, higher up-front costs of integrative treatment approaches may be potentially offset by improved work productivity and increased future Quality Adjusted Life Years (QALYs) [96].…”
Section: Integrative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, systematic reviews of economic modelling studies on comparative cost-effectiveness of conventional versus integrative treatments of many health conditions (including mental illness), suggest that integrative treatments are cost-effective, and in some cases, provide cost savings [42]. Individual lifestyle interventions have also demonstrated cost-effectiveness [98,99]. Finally, higher up-front costs of integrative treatment approaches may be potentially offset by improved work productivity and increased future Quality Adjusted Life Years (QALYs) [96].…”
Section: Integrative Medicinementioning
confidence: 99%
“…Finally, higher up-front costs of integrative treatment approaches may be potentially offset by improved work productivity and increased future Quality Adjusted Life Years (QALYs) [96]. Further, cost-effectiveness of individual lifestyle interventions has also been demonstrated [98,99].…”
Section: Integrative Medicinementioning
confidence: 99%
“…This study also showed a cost savings of ~$2500 per participant in favour of the dietary intervention due to reduced healthcare costs and reduced productivity costs (e.g., missed fewer paid and unpaid work days) [23]. A larger, group-based study using a similar approach reported very comparable findings and was also highly costeffective [25]. In addition, these studies are now corroborated by meta-analytic evidence, including data from 16 RCTs and 45,826 participants, showing that dietary improvement is also an efficacious treatment option for sub threshold depression [6], especially when delivered by accredited nutritionists or dietitians.…”
Section: Evidence Base For the Use Of Lifestyle Programs In Mental Healthmentioning
confidence: 55%
“…In the HELFIMED study, a 3-month group-based Mediterranean-style diet intervention, healthy dietary changes supplemented with fish oil were found to be beneficial for treating depressive symptoms [29]. In the same study, the intervention group participating in cooking workshops was cost-effective compared to a social support group [21].…”
Section: Background and Rationale {6a}mentioning
confidence: 96%
“…Although there is little evidence of the financial benefits brought by a dietary intervention for treating depression, there are two recently published studies on the matter. One of them indicated that dietary treatment was highly cost-effective in treating major depression compared to a social support group program [21], while the other produced the same amount of QALYs with lower costs [22].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%